Pelatihan Inovasi Pangan dan Kosmetik Alami untuk Peningkatan Kesehatan dan Ekonomi Keluarga di Wilayah Baciro - Brigitta Laksmi Paramita; Nelsiani To'bungan; Agatha Mayasari; Benediktus Yudo Leksono; Jevon Fausto Gunawan; Vanesa Risna Sabatania; Bernadeta Dian Fajar Novitaningrum (Jurnal Atma Inovasia, 2026)
The Baciro area has residents who are housewives and socially active. However, access to information and healthy living practices is still limited. In addition, the development of economic skills and family health practices has not been specifically directed. This community service program aims toa empower the housewives of the Paroki Gereja Kristus Raja Baciro, Yogyakarta, through training in food and cosmetic innovations using natural ingredients. The activities focus on improving nutrition literacy, developing skills in producing dried noodles made from freshwater fish, creating rose-based facial masks, and strengthening household entrepreneurship capacity. The implementation methods include outreach, training, technology application, assistance, and evaluation. The results of the program show a significant increase in participants’ knowledge, the creation of prototypes of healthy noodle products and natural facial masks, and the development of a social media account and marketing attributes such as product posters and stickers as promotional tools. Evaluation was carried out at each stage and overall, with a sustainability plan through post-program monitoring. This program contributes to improving skills, as evidenced by the increased number of business groups related to the products introduced.